Staphylococcus aureus and MRSA Growth and Biofilm Formation after Treatment with Antibiotics and SeNPs - Cihalova, Kristyna; Chudobova, Dagmar; Michalek, Petr; Moulick, Amitava; Guran, Roman; Kopel, Pavel; Adam, Vojtech; Kizek, Rene (International journal of molecular sciences, 2015)
Methicillin-resistant Staphylococcus aureus (MRSA) is a dangerous pathogen resistant to β-lactam antibiotics. Due to its resistance, it is difficult to manage the infections caused by this strain. We examined this issue in terms of observation of the growth properties and ability to form biofilms in sensitive S. aureus and MRSA after the application of antibiotics (ATBs)-ampicillin, oxacillin and penicillin-and complexes of selenium nanoparticles (SeNPs) with these ATBs. The results suggest the strong inhibition effect of SeNPs in complexes with conventional ATBs. Using the impedance method, a higher disruption of biofilms was observed after the application of ATB complexes with SeNPs compared to the group exposed to ATBs without SeNPs. The biofilm formation was intensely inhibited (up to 99%±7% for S. aureus and up to 94%±4% for MRSA) after application of SeNPs in comparison with bacteria without antibacterial compounds whereas ATBs without SeNPs inhibited S. aureus up to 79%±5% and MRSA up to 16%±2% only. The obtained results provide a basis for the use of SeNPs as a tool for the treatment of bacterial infections, which can be complicated because of increasing resistance of bacteria to conventional ATB drugs.
Keywords: selen; Selenium; Methicillin-Resistant Staphylococcus aureus; biofilmy; methicillin-resistant Staphylococcus aureus; Biofilms; Anti-Bacterial Agents; mikrobiální testy citlivosti; Microbial Sensitivity Tests; selenium nanoparticles; antibiotics; Nanoparticles; methicilin rezistentní Staphylococcus aureus; Staphylococcus aureus; antibakteriální látky; nanočástice